Factors affecting e-Learning effectiveness in a higher learning institution in Malaysia - Md. Aminul Islam,; Chuthamas Chittithaworn,; Ahmad Zulhusny Rozali,; Hee Liang, (penerbit ukm, 2010)
The purpose of this research was to investigate factors that influence the effectiveness of the e-learning system in a higher learning institution. The participants were students randomly selected from diploma and degree programs. The main instrument was a questionnaire that was distributed to the students. The researchers collected 205 completed questionnaires out of a total of 300. Four factors were chosen as independent variables namely: reaction and satisfaction,learning outcome and achievement, familiarity with online learning technology, and participation and interaction. It was found that the effectiveness of the e-learning system was significantly affected by reaction and satisfaction, learning outcome and achievement, and familiarity with online learning technology. The participation and interaction factor had no apparent effect on the effectiveness of the e-learning system. Therefore, it is recommended that higher learning institutions interested in introducing e-learning should focus on students’ reaction and satisfaction towards the system.E-learning should focus on learning outcomes and achievement. It is also recommended that institutions first look into the issue of familiarity with online learning technology among students before introducing the e-learning system so as to determine whether students are comfortable with the online learning tools.